2020
DOI: 10.7554/elife.56477
|View full text |Cite
|
Sign up to set email alerts
|

Private–public mappings in human prefrontal cortex

Abstract: A core feature of human cognition is an ability to separate private states of mind – what we think or believe – from public actions – what we say or do. This ability is central to successful social interaction – with different social contexts often requiring different mappings between private states and public actions in order to minimise conflict and facilitate communication. Here we investigated how the human brain supports private-public mappings, using an interactive task which required subjects to adapt h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 54 publications
4
29
0
Order By: Relevance
“…While the representation in dACC may serve to inform internal models and response selection [39][40][41][42] , it seems likely that dAI integrates uncertainty with interoceptive and affective information to form a general subjective feeling state 22 . rlPFC, on the other hand, likely plays a key role in the integration of internal uncertainty with contextual information to compute confidence 32,36,[43][44][45] .…”
Section: Discussionmentioning
confidence: 99%
“…While the representation in dACC may serve to inform internal models and response selection [39][40][41][42] , it seems likely that dAI integrates uncertainty with interoceptive and affective information to form a general subjective feeling state 22 . rlPFC, on the other hand, likely plays a key role in the integration of internal uncertainty with contextual information to compute confidence 32,36,[43][44][45] .…”
Section: Discussionmentioning
confidence: 99%
“…In particular, we found that, at the time of making a perceptual estimate, dACC tracked participants’ confidence in this estimate – a temporal association identified by other studies on the neural basis of decision confidence (18). However, recent research, which disentangled the components of decision confidence (28) or separated a sense of confidence from explicit confidence reports (17), suggest that this temporal association is due to a role of dACC in controlling confidence-based behaviours rather than encoding a sense of confidence per se. However, we acknowledge that our whole-brain analysis did not reveal any other brain regions that may have supported a confidence computation.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation distance metric was chosen as a measure that is magnitude insensitive to the BOLD signal, and thus makes separate predictions from the univariate trial-by-trial model-based analysis or by using alternative distance metrics such as Euclidean distance 57,66 . As in previous RSA studies 54,[99][100][101] the diameter of the searchlight sphere was 15 mm (approximately 100 voxels) and we used the group level mask to define the volume for the searchlight analysis. The brain searchlight maps were correlated with each behavioural RDM using Kendall's Tau-a to parallel the ROI analysis.…”
Section: Imaging Design: Multivariate Analysismentioning
confidence: 99%